2022
DOI: 10.1002/ps.6846
|View full text |Cite
|
Sign up to set email alerts
|

The gut commensal bacterium Enterococcus faecalis LX10 contributes to defending against Nosema bombycis infection in Bombyx mori

Abstract: BACKGROUND: Microsporidia, a group of obligate intracellular fungal-related parasites, have been used as efficient biocontrol agents for agriculture and forestry pests due to their host specificity and transovarial transmission. They mainly infect insect pests through the intestinal tract, but the interactions between microsporidia and the gut microbiota of the host have not been well demonstrated.RESULTS: Based on the microsporidia-Bombyx mori model, we report that the susceptibility of silkworms to exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In mosquitoes, ROS, metabolites, small peptides, and proteins secreted by gut bacteria may directly influence the transmission and development of pathogens [ 98 ]. A recent study also confirmed that the Bombyx mori intestinal commensal Enterococcus faecalis LX10 significantly reduced the germination rate and effectiveness of infection by the microsporidium Nosema bombycis [ 99 ]. Meanwhile, intestinal commensal bacteria activate the Imd–Relish immune pathway to balance the regeneration of intestinal epithelial cells caused by pathogenic bacteria [ 100 ].…”
Section: Gut Microbesmentioning
confidence: 83%
“…In mosquitoes, ROS, metabolites, small peptides, and proteins secreted by gut bacteria may directly influence the transmission and development of pathogens [ 98 ]. A recent study also confirmed that the Bombyx mori intestinal commensal Enterococcus faecalis LX10 significantly reduced the germination rate and effectiveness of infection by the microsporidium Nosema bombycis [ 99 ]. Meanwhile, intestinal commensal bacteria activate the Imd–Relish immune pathway to balance the regeneration of intestinal epithelial cells caused by pathogenic bacteria [ 100 ].…”
Section: Gut Microbesmentioning
confidence: 83%
“…Enterococcus have also been reported to increase larval defense of Bombyx mori to biological control and removal of the Enterococcus symbiont from the larvae would increase the success of biocontrol of this insect larvae 84 . Enterococcus and Lactococcus can protect insect larvae against pathogens, plant toxins and increase host fitness 54 , 85 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also revealed the importance of the silkworm gut microbiome in various aspects of host physiology, including nutrient metabolism, disease resistance, and immune defense [25] , [54] , [58] , [59] . Exposure to PS-MNPs can change the structure of the microbial community, with smaller particles having a stronger impact.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of genera Acinetobacter and Enterococcus in the exposure groups, positively correlated with body weight, suggests that they might be potential biomarkers for obesity. These taxa have health-promoting potential and an improved capacity for energy harvest and storage, leading to increased caterpillar body weights [54] , [58] , [59] , [62] , [63] . In accordance with our study, these taxa were strongly associated with the gut microbiota of G. mellonella, Tenebrio molitor, and Tribolium castaneum which had consumed PS-MNPs and other kinds of plastics [21] , [22] , [64] .…”
Section: Discussionmentioning
confidence: 99%